Energy transfer process between two laser compounds coumarin 334 & rhodamine 590 - Ali AL Tememee, Nathera Abass (Iraqi Journal of Physics, 2019)
In the current research the absorption and fluorescence spectrumof Coumarin (334) and Rhodamine (590) in ethanol solvent atdifferent concentration (10-3, 10-4, 10-5) M had been studied. Theabsorption intensity of these dyes increases as the Concentrationincrease in addition to that the spectrum was shifted towards thelonger wavelength (red shift). The energy transfer process has beeninvestigated after achievement this condition. The fluorescence peakintensity of donor molecule was decrease and its bandwidth willincreases on the contrary of the acceptor molecule its intensityincrease gradually and its bandwidth decreases as the acceptorconcentration increase.